Pelatihan Penanaman Tanaman Apotek Hidup Di Lahan Pekarangan Rumah Warga Desa Ngandul Sumberlawang Sragen - Hikmawati, Hanifah; Sulastri, Sulastri (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Living pharmacies focus on the use of medicinal plants and spices that can be grown at home or in the surrounding environment to support the health and welfare of the community. Medicinal plants have long been used as traditional medicine in various cultures around the world. Living pharmacies are emerging as an attractive option with increasing interest in holistic health and sustainability. Many medicinal plants contain bioactive compounds that have medical benefits such as anti-inflammatory, antioxidant and antimicrobial. This research uses a participatory approach with the following steps: (1) Needs assessment through observations and interviews with local communities, (2) Implementation of training and workshops regarding medicinal plant cultivation techniques and the health benefits of plants, (3) Making living pharmacies by planting various medicinal plants in several home yards, gardens, parks, and (4) Monitoring and evaluating the impact of training and implementation of living pharmacies. Participants showed increased knowledge regarding the benefits of medicinal plants and the ability to cultivate and utilize these plants. People are starting to use medicinal plants for their daily health needs.